Participatory Urban Planning: What Would Make Planners Trust the Citizens? - Åström, Joachim (2020)
Based on the critical stance of citizens towards urban planning, growing attention has been directed towards new forms of citizen participation. A key expectation is that advanced digital technologies will reconnect citizens and decision makers and enhance trust in planning. However, empirical evidence suggests participation by itself does not foster trust, and many scholars refer to a general weakness of these initiatives to deliver the expected outcomes. Considering that trust is reciprocal, this article will switch focus and concentrate on planners’ attitudes towards citizens. Do urban planners generally think that citizens are trustworthy? Even though studies show that public officials are more trusting than people in general, it is possible that they do not trust citizens when interacting with government. However, empirical evidence is scarce. While there is plenty of research on citizens’ trust in government, public officials trust in citizens has received little scholarly attention. To address this gap, we will draw on a survey targeted to a representative sample of public managers in Swedish local government (N = 1430). First, urban planners will be compared with other public officials when it comes to their level of trust toward citizens’ ability, integrity and benevolence. In order to understand variations in trust, a set of institutional factors will thereafter be tested, along with more commonly used individual factors. In light of the empirical findings, the final section of the article returns to the idea of e-participation as a trust-building strategy. What would make planners trust the citizens in participatory urban planning?